Best Practice Policy Guidance for Liquefied Natural Gas (LNG) - United Nations (United Nations, 2018)
Natural gas, including liquefied natural gas (LNG), has clear environmental benefits over other, more carbon-intensive fossil fuels. Substituting other fossil fuels by natural gas can substantially reduce emissions of carbon dioxide and of other pollutants (particulate matter, and oxides of nitrogen and sulfur) and contribute to the decarbonisation policy objectives. Regasification terminals can play a key role in ensuring security of supply, diversification of supply, as well as enabling the integration of renewable energy. This publication looks into a case study in truck loading.